Research on the effect of different types of short music videos on viewers' psychological emotions - Ma, Lin (Frontiers in Public Health, 2022)
There is now widespread agreement that different types of short music videos can cause viewers to have psychological emotions, and significant new findings have been discovered in the study of how music affects listeners' affective reactions. However, there is still controversy regarding research on the inclinations toward behavior and autonomic neurophysiological reactions of musical emotions. The psychological states of viewers of various types of short music videos are yet unknown and require further study. This study investigates how different types of short music videos affect viewers' psychological responses, placing particular emphasis on the following variables: rhythm type (stable rhythm and flow rhythm) and music short video type (narrative, live, and funny). In an experiment, viewers' psychological responses to several short music videos were investigated to determine the impact of different short music video styles and rhythms on musically induced emotions.